(untitled) (Global Journal of Science Frontier Research, 2017)
Three hundred day-old black Harco cockerel chicks were started on a standard fish meal diet containing 2.65 Kcal/g ME at 21% crude protein for the first four weeks. At the end of which one hundred and forty of the birds were allocated to another diet of 2.65 Kcal/g ME at same 21% protein but without fish meal. The remaining 160 birds were maintain alongside on a fish meal diet containing 2.65Kcal/g ME and 21% protein till they were eight weeks old. At the finisher phase the two set of birds were assigned to eight experimental rations in a 4×2 factorial design; differently maintained. The diets were a control which contain fish meal and groundnut meal (GNM) as the major protein source. The next had only GNM as the major protein source. In the next consecutive diets, one-third, two-third and all of the GNM protein contribution was replaced by corresponding protein value of cotton seed meal (CSM) and palm Kernel meal (PKM).